The uses of curiosity in early modern France and Germany - Kenny, Neil (Oxford University Press, 2004)
Between the 16th and 18th centuries, writers obsessively discussed curiosity in order to regulate knowledge or behaviour to establish who should try to know or do what. This title investigates that obsession by developing a language based approach that contributes to debates about knowledge we can have of the past.